WIRELESS COMPUTING TOOL WITH RFID AND ESP32 IN SUPPORT OF LITERACY: A QUALITATIVE CASE STUDY - Kuss, Paulo Fernando; Salete, Maria; Henriques, Renato Ventura Bayan (Seven Editora, 2025)
The objective of this study was to evaluate the application of a tangible, wireless educational technology, based on ESP32 and RFID, to support the literacy process of children with writing difficulties. The research was conducted in a public school, involving ten third- and fourth-grade students and a literacy teacher. Over ten workshops, the technology mediated reading, writing, and phonological awareness activities. The children were assisted in tasks such as reading, writing words, and recognizing letter sounds. The results demonstrated that the technology proved to be a highly effective resource in the literacy process. Data collection included observations of the participants, analysis of written productions, records of correct and incorrect answers, and evaluation of student progress by the literacy teacher. Content analysis was used, which indicated significant advances in phonological awareness, self-correction, autonomy, and engagement of the children. Among the most relevant occurrences was the advancement in understanding the grapheme-phoneme relationship. The tangible interface, combined with instant auditory feedback, promoted greater participation and focus, allowing for longer work periods with less need for researcher intervention. The teacher evaluated the tool as easy to use, requiring low infrastructure, and applicable to different school contexts. The study thus highlights the potential of tangible educational technologies as cognitive mediators in the initial literacy process of children with learning difficulties, while also emphasizing the importance of continuous teacher training.DOI: https://doi.org/10.56238/sevened2025.036-071